Sexual Violence Among Higher Education Students in the United Kingdom: Results from the Oxford Understanding Relationships, Sex, Power, Abuse and Consent Experiences Study - Steele, Bridget (Journal of interpersonal violence, 2024)
Sexual violence (SV) experienced by higher education students is a prevalent public health problem. Collecting data on SV through self-report surveys in higher education institutions (HEIs) is essential for estimating the scope of the problem, the first step to adequately resourcing and implementing prevention and response programming and policies. However, in the United Kingdom, data is limited. We used data from the cross-sectional Oxford Understanding Relationships, Sex, Power, Abuse and Consent Experiences survey, administered to all students at a university in the United Kingdom in May 2021 (n = 25,820), to estimate the past year prevalence of SV. We analyzed data from respondents who answered at least one question on SV (n = 1,318) and found that 20.5% of respondents experienced at least one act of attempted or forced sexual touching or rape, and 52.7% of respondents experienced at least one act of sexual harassment (SH). We found that women experienced the highest rates of SV. Attempted forced sexual touching was far more common than forced sexual touching, or rape. Sexist remarks or jokes were the most common act of SH. Most acts of SV took place at the university. These findings reveal that the prevalence of SV in HEIs in the United Kingdom could be far higher than what is experienced in the general population. While this study reflects the context in only one institution, it underlines the need for continued monitoring to develop rigorous, evidence-based, and targeted prevention and response strategies.